Evaluation of semiconducting molecular thin films solution-processed via the photoprecursor approach: the case of hexyl-substituted thienoanthracenes1. Issue 23 (21st June 2015) - Quinton, Cassandre; Suzuki, Mitsuharu; Kaneshige, Yoshitaka; Tatenaka, Yuki; Katagiri, Chiho; Yamaguchi, Yuji; Kuzuhara, Daiki; Aratani, Naoki; Nakayama, Ken-ichi; Yamada, Hiroko
<x xml:space="preserve">Abstract</x> The photoprecursor approach is superior to direct spin coating in preparing high quality organic semiconducting thin films.